Effects of alternate moistube-irrigation on soil water infiltration - Shen, Lixia; Zhang, Yumeng; Yang, Mei; Liu, Ronghao (International Journal of Agricultural and Biological Engineering, 2020)
Alternate moistube-irrigation is a new type of water-saving irrigation, and research on water infiltration with alternate moistube-irrigation is important for the design of irrigation schemes and helpful to understand and apply this technology. The effects of the pressure head (1.0 m and 1.5 m) and tube spacing (10 cm, 20 cm, and 30 cm between two moistubes respectively) on soil water infiltration in alternate moistube-irrigation were studied in laboratory experiments, and the cumulative infiltration, discharge of the moistube, and shape and water distribution of the cross-section of the wetting front were determined. The cumulative infiltration increased quickly and linearly with the infiltration time at 0-96 h (R2>0.99), and changed smoothly at 96-192 h with a basically steady infiltration rate. The discharge of the moistube increased rapidly at the beginning of irrigation, then decreased before stabilizing. The cumulative infiltrations and discharges of moistube under the 1.5 m pressure head were more than those under the 1.0 m pressure head. The shape of the cross-section of the wetting front for a single moistube was similar to a concentric circle. With the increase of tube spacing, the interaction between water infiltrations of two moistubes decreased. The soil water distributions around two moistubes were similar to each other under the 1.0 m pressure head and large tube spacing. When the tube spacing was 20 cm, the soil water distribution was more uniform around two moistubes. Keywords: alternate irrigation, moistube-irrigation, soil water infiltration, water use efficiency, water-saving irrigation DOI: 10.25165/j.ijabe.20201304.5297 Citation: Shen L X, Zhang Y M, Yang M, Liu R H. Effects of alternate moistube-irrigation on soil water infiltration. Int J Agric & Biol Eng, 2020; 13(4): 151–158.